Improving canal irrigation performance with on-farm water storage: evidence from the Indira Gandhi Nahar Pariyojana Project in India - Amarasinghe, Upali A.; Kuppannan, Palanisami; Singh, Om Prakash (Wiley, 2012)
On-farm water storage (OFWS) is a farmers' response to mitigating inadequate and variable water supply in canal commands in the Indira Gandhi Nahar Pariyojana project in Rajasthan, India. This paper assesses the impact of OFWS on on-farm performance, based on a sample of farms with and without storage tanks. OFWS facilitated the use of sprinklers, and the use of both together contributed to an improved level of on-farm water control and timing of inputs, which resulted in an increase in gross irrigated area and crop yields. As a result, the average net value of output per hectare is 56% higher in farms with the new infrastructure. This is a financially viable intervention for farms with an irrigable area larger than 5 ha, with a benefit?cost ratio of 2.2 and internal rate of return of 35%. OFWS can be a catalyst for rejuvenating canal irrigation schemes with low on-farm performance.